Type 1 Diabetes incidence among youth in Utah: A geographical analysis. (June 2021) - McCullough, Matthew L.; Wan, Neng; Pezzolesi, Marcus G.; Collins, Timothy W.; Grineski, Sara Elizbeth; Wei, Yehua Dennis; Lazaro-Guevara, Jose; Frodsham, Scott G.; Vanderslice, James A.; Holmen, John R.; Srinivas, Titte R.; Clements, Scott A.
Abstract: Type 1 Diabetes (T1D) poses an increasing threat to public health, as incidence rates continue to rise globally. However, the etiology of T1D is still poorly understood, especially from the perspective of geography. The objective of this research is to examine the incidence of T1D among youth and to identify high-risk clusters and their association with socio-demographic and geographic variables. The study area was the entire state of Utah and included youth with T1D from birth to 19 years of age from 1998 to 2015 (n = 4161). Spatial clustering was measured both globally and locally using the Moran's I statistic and spatial scan statistic. Ordinary least squares (OLS) regression was used to measure the association of high-risk clusters with certain risk factors at the Census Block Group (CBG) level. The mean age at diagnosis was 9.3 years old. The mean incidence rate was 25.67 per 100, 000 person-years (95% CI, 24.57–26.75). The incidence rate increased by 14%, from 23.94 per100, 000 person-years in 1998 to 27.98 per 100, 000 person-years in 2015, with an annual increase of 0.80%. The results of the spatial scan statistic found 42 high-risk clusters throughout the state. OLS regression analysis found a significant association with median household income, population density, and latitude. This study provides evidence that incidence rates of T1D are increasing annually in the state of Utah and that significant geographic high-risk clusters are associated with socio-demographic and geographic factors. Highlights: Determines incidence rates for Type 1 Diabetes among youth in Utah, U.S.A. Identifies spatial hotspots of Type 1 Diabetes at the Census Block Group level. Measures association of incidence rates with socio-demographic risk factors. Measures association of incidence rates with geographic risk factors.